If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2m = -3 + -4m Solving 9 + 2m = -3 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. 9 + 2m + 4m = -3 + -4m + 4m Combine like terms: 2m + 4m = 6m 9 + 6m = -3 + -4m + 4m Combine like terms: -4m + 4m = 0 9 + 6m = -3 + 0 9 + 6m = -3 Add '-9' to each side of the equation. 9 + -9 + 6m = -3 + -9 Combine like terms: 9 + -9 = 0 0 + 6m = -3 + -9 6m = -3 + -9 Combine like terms: -3 + -9 = -12 6m = -12 Divide each side by '6'. m = -2 Simplifying m = -2
| x(x+3)-5(x+3)= | | 45=0.5(6+3) | | -9x=-27 | | 6(k-5)-(2k-4)=7k | | 9(y-7)=8+8y | | 6y+1-2y=8+3y+6 | | -9(n-6)=-8n-9 | | 4y+3y=6y+3 | | -3(4x-6)+8=-12x+26 | | 0.12(y-7)+0.04y=0.20y-0.9 | | 10x^3-8x^2+2x=0 | | 34X-25=18 | | -9(x-8)+2=74 | | 2(4x+7)-5=8x+9 | | -x+3=22 | | 15t^4-2t^2+78=0 | | n/2-9=-5 | | 30=48t-16t^2 | | 3(2x+35)+5(x+1)=u | | (15+9)x(22-5)= | | u/12-8=-8 | | 44=2(3.14) | | -8(t-4)-(t+1)=4 | | 6x-4=24x+2 | | 5(x+2)+7=17 | | r/2+6=5 | | 6(2x+33)+7(x+1)=u | | 3x^2+5=21 | | 50.2=2(3.14) | | 9(x-4)+4=-32 | | 12x-2=24x+7 | | 6(2x+30)+7(x+1)=u |